2021
DOI: 10.3389/fcell.2021.665412
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hyperglycemia in the Senescence of Mesenchymal Stem Cells

Abstract: The regenerative and immunomodulatory properties of mesenchymal stem cells (MSCs) have laid a sound foundation for their clinical application in various diseases. However, the clinical efficiency of MSC treatments varies depending on certain cell characteristics. Among these, the roles of cell aging or senescence cannot be excluded. Despite their stemness, evidence of senescence in MSCs has recently gained attention. Many factors may contribute to the senescence of MSCs, including MSC origin (biological niche)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 83 publications
2
23
0
Order By: Relevance
“…That can be related to what is described by other studies, showing that bone marrow MSC cultures in high glucose concentrations increase cellular senescence [80]. This may have a negative impact on regenerative capacity under hyperglycemic conditions, mainly in diabetic patients [81].…”
Section: Discussionsupporting
confidence: 80%
“…That can be related to what is described by other studies, showing that bone marrow MSC cultures in high glucose concentrations increase cellular senescence [80]. This may have a negative impact on regenerative capacity under hyperglycemic conditions, mainly in diabetic patients [81].…”
Section: Discussionsupporting
confidence: 80%
“…Hyperglycemia, one of the most prominent features of the diabetic milieu, has been shown to alter MSC’s characteristics and functions and result in MSC senescence. 182 , 183 In a hyperglycemic environment, adipose-derived MSCs (AD-MSCs) have been shown to display a decreased proliferative profile and a greater rate of senescence which highly reduced their therapeutic efficiency. 184 Besides, it has been reported that AD-MSCs under hyperglycemic settings demonstrate diminished immunomodulatory capabilities, angiogenesis, and migratory capacity, as well as increased SASP and insulin resistance.…”
Section: Mechanisms Of Msc Senescencementioning
confidence: 99%
“…The inflammation, ROS overproduction, and advanced glycation end-products (AGEs) caused by hyperglycemia were considered as major contributors to the complications’ etiologically, as they impair vascular function directly [ 19 ]. On the other hand, inflammation, ROS, and AGEs are well-known to promote cellular senescence, and actually, hyperglycemia-induced endothelial cell senescence was observed in vascular cells, such as endothelial cells [ 10 , 20 , 21 , 22 , 23 ], smooth muscle cells [ 11 ], endothelial progenitor cells [ 12 ], and mesenchymal stem cells [ 13 ]. These observations suggest that senescence may be serving as a shared downstream link to diabetic complications.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that hyperglycemia promotes inflammation and the production of reactive oxidative species (ROS) through multiple regulatory mechanisms, impairing vascular cells (endothelial cell and smooth muscle cell) that eventually damage vascular function [ 3 , 5 , 6 , 7 , 8 , 9 ]. In addition, there is growing evidence that hyperglycemia induces premature senescence in endothelial cells [ 10 ], smooth muscle cells [ 11 ], endothelial progenitor cells [ 12 ], and mesenchymal stem cells [ 13 ], suggesting that cellular senescence in vessels may play an important role in the process of diabetic complications. The mechanism by which hyperglycemia promotes senescence is yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%